Sheikh Bin Wan Ismail Wan Abdul Qadir (d. 1965) And His Efforts in the Field of Islamic Faith - Mujahid Mustafa Bahjat; Mosidi Sally Bin Saleh (UIN Sunan Gunung Djati Bandung, 2013)
Wan Ismail Shaikh Abdul Qadir was one of the Ulema, he known to struggle in spreading Islamic Aqedah and development in the Patani region in particular and generally in Malay region, this study will provide an overview of his life and contribution to science, and also the study of the struggle to spread knowledge in the Islamic faith. One of the relics of his work is